The Effect Of The PBK (Character Learning Project) Learning Model On The Ability To Write News Texts Of Grade VIII - Amorianda Simbolon; Martua Reynhat Sitanggang Gusar; Pontas Jamaluddin Sitorus (STABN RADEN WIJAYA WONOGIRI, 2024)
The purpose of this study was to determine the effect of using the PBK (Character-Based Project Learning) model on the ability to write news texts among Grade VIII students of Hosana Private Junior High School Medan in the 2025/2026 academic year. The population consisted of five classes with a total of 130 students, from which a sample of 31 students (class VIIIB) was selected using simple random sampling.The method used in this study was a one-group pretest-posttest design. The research aimed to assess students’ ability to write news texts. The data were collected through a performance test instrument.The results of data analysis showed that the students’ average pretest score before using the PBK model was 60, while the average posttest score increased to 80. Hypothesis testing using the “T” indicated that T_(hitung > ) T_tabel (11.058) > (1.670649). Based on these results, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Thus, it can be concluded that the PBK (Character-Based Project Learning) model significantly influences the students’ ability to write news texts in Grade VIII of Hosana Private Junior High School Medan.